Trends in the use of antibiotics among Korean children - Young June Choe; Ju-Young Shin (Korean Pediatric Society, 2019)
Inappropriate antibiotic use is the most important factor causing increased bacterial resistance to antibiotics, thus affecting patient outcomes. Multidrug-resistant bacteria have become a serious public health threat, causing significant morbidity and mortality worldwide. In Korea, the burden of antibioticresistant bacteria has become an important public health issue. There is increasing evidence of overuse and misuse of antibiotics in Korea, as observed in cohorts with large sample sizes. Antibiotic use among children should receive particular attention because of the frequency of community-associated infections among this population and the elevated risk of transmission. Recent studies from Korea have demonstrated that the use of broad-spectrum antibiotics, either for inpatient or outpatient treatment, has increased among many age groups, especially children. In this review, we aim to describe the patterns of antibiotic prescription and evaluate recent trends in antibiotic use among children. Coordinated efforts toward communication and education in order to address misunderstandings regarding antibiotic use, involving interprofessional antimicrobial stewardship programs, are required in the near future.